Fatigue failure characterization of multi-axial warp-knitted composites under cyclic uniaxial tensile loading. Issue 5 (4th May 2019) - Lingxiao, Jing; Penghu, Deng; Yi, Wang; Dan, Li; Zaixing, Zhang
Abstract: In this work, the fatigue failure mechanisms of quadri- and tri-axial warp-knitted fabric composites (QWFC and TWFC) were investigated. A series of quasi-static state tensile tests and cyclic loading experiments were carried out, and the morphology of fatigue failure was visualized by optical and scanning electron microscopes (SEM). The results showed that while the failures of QWFC and TWFC were similar with X-shape morphology, QWFC had longer fatigue life than TWFC. The SEM images illustrated that the matrix of QWFC was not uniform, and contained cracks with scaly appearance, in addition to small amount of fiber curls. Moreover, the fracture surface was flat and layered. In contrast, the matrix of TWFC had propagation of cracks along ±45° direction; its fracture surface had sphere 'budding yeast-like' appearance. The wrap-knitted fabric contained increased numbers of layers in the composites, thereby had longer fatigue life.